STUDENTS’ DIFFICULTIES IN LEARNING PHONETICS AT THE ENGLISH EDUCATION DEPARTMENT OF UNIVERSITAS MUHAMMADIYAH YOGYAKARTA - Oktanika Wahyu Nurjanah (PBI 15 UMY 022, 2015)
*22 The comprehensible and acceptable pronunciation is definitely important in communication. Furthermore, English pronunciation is explored in one of the linguistic branches, namely Phonetics. Moreover, phonetics has some difficulties such remembering the IPA, place and manner. Therefore, this research tried to reveal the difficulties faced by students in learning the phonetics at the English Education Department of UMY. To collect the data in this qualitative research, an in-depth interview was used and it was supported with the phonetic test. Moreover, the data collected from six students of English Education Department of UMY batch 2014. Furthermore, the data were analyzed through verbatim transcription and some steps of coding, they are open coding, axial coding and selective coding. Additionally, the result were categorized based on the theory and described in paragraph. This research reveled four difficulties faced by students in learning phonetics, they are difficulty in sound production, difficulty in code selection, difficulty in word interpretation, and difficulty in phoneme identification. In addition, there are five factors causing the difficulties of phonetics, namely the complicated system, word meaning, unfamiliarity, odd appearance, and first language. At last, because of the difficulties and the factors of phonetics, the researcher also provides some recommendation for the students, lecturers, institution and also STUDENTS’ DIFFICULTIES IN LEARNING PHONETICS xii the future researchers. Students and lecturers should habituate and maximize the use of Phonetics. For the institution, they should increase the frequency of Phonetics learning. Finally, for the future researchers need to dig the study related to Phonetics it self.